Heavy metal contamination in soils and food crops around Dabaoshan mine in Guangdong, China: implication for human health - Zhuang, P; Zou, B; Li, N. Y; Li, Z. A (Environmental geochemistry and health, 2009)
This study was designed to investigate heavy metal (Cu, Zn, Pb, and Cd) contamination levels of soils, vegetables, and rice grown in the vicinity of the Dabaoshan mine, south China. The concentration of Cu, Zn, Pb, and Cd in paddy soil exceeded the maximum allowable concentrations for Chinese agricultural soil. The heavy metal concentrations (mg kg⁻¹, dry weight basis) in vegetables ranged from 5.0 to 14.3 for Cu, 34.7 to 170 for Zn, 0.90 to 2.23 for Pb, and 0.45 to 4.1 for Cd. The concentrations of Pb and Cd in rice grain exceeded the maximum permissible limits in China. Dietary intake of Pb and Cd through the consumption of rice and certain vegetable exceeded the recommended dietary allowance levels. The status of heavy metal concentrations of food crops grown in the vicinity of Dabaoshan mine and their implications for human health should be further investigated.